The Royal College of Ophthalmologists’ National Ophthalmology Database study of cataract surgery: report 4, equity of access to cataract surgery - Johnston, Robert L. (Eye (Lond), 2019)
OBJECTIVE: To determine whether socioeconomic status influenced the presenting visual acuity prior to first eye cataract surgery in the English National Health Service. Retrospective case series from The Royal College of Ophthalmologists’ National Ophthalmology Database Audit. In total 154,223 patients undergoing first eye cataract surgery at 68 centres in England performed between 1st September 2015 and 31st August 2017. MAIN OUTCOME MEASURE: Social deprivation status and pre-operative visual acuity (VA) between centres for patients undergoing first eye cataract surgery in England. RESULTS: The median social deprivation varied between centres and ranged from decile 2 (2nd most deprived decile) to decile 9 (2nd least deprived decile). The pre-operative VA was reported for 143,401 (93.0%) eyes. The median pre-operative VA was 0.50 LogMAR (6/19), and 27.7% eyes had a preoperative VA of 0.30 LogMAR units (6/12) or better. The median pre-operative VA for each centre ranged from 0.30 to 0.60 LogMAR (6/12 to 6/24). The median pre-operative VA was mostly stable across deciles of social deprivation (0.60 LogMAR for decile 1 and 0.50 LogMAR for all other deciles), and some evidence was found linking greater deprivation to worse pre-operative VA and to lower levels of access. CONCLUSIONS: We found no strong evidence of inequality for gaining access to first eye cataract surgery in this National Ophthalmology Database analysis, however there was a possible trend towards fewer people in the more deprived deciles accessing surgery, and that some of these are presenting with quite marked levels of visual impairment.